An immersed boundary-based large-eddy simulation approach to predict the performance of vertical axis tidal turbines. (18th July 2017) - Ouro, Pablo; Stoesser, Thorsten
Highlights: A LES solver is equipped with an IB method to predict the performance of VATTs. The method is validated with body-fitted models for a VATT in a laminar flow. Simulations of a VATT under turbulent flow confirmed the method's accuracy. LES-IB method results overcome RANS predictions with a closer match with experiments. Blade-vortex interaction visualisations highlight the complex flow around VATTs. Abstract: Vertical axis tidal turbines (VATTs) are perceived to be an attractive alternative to their horizontal axis counterparts in tidal streams due to their omni-directionality. The accurate prediction of VATTs demands a turbulence simulation approach that is able to predict accurately flow separation and vortex shedding and a numerical method that can cope with moving boundaries. Thus, in this study an immersed boundary-based large-eddy simulation (LES-IB) method is refined to allow accurate simulation of the blade vortex interaction of VATTs. The method is first introduced and validated for a VATT subjected to laminar flow. Comparisons with highly-accurate body-fitted numerical models results demonstrate the method's ability of reproducing accurately the performance and fluid mechanics of the chosen VATT. Then, the simulation of a VATT under turbulent flow is performed and comparisons with data from experiments and results from RANS-based models demonstrate the accuracy of the method. The vortex-blade interaction is visualised for various tip speed ratios and together with velocity spectra detailed insights into the fluid mechanics of VATTs are provided.